Diagnostic, Treatment, and System Challenges in the Management of Recurrent Neuroleptic Malignant Syndrome on a General Medical Service - Karan Verma; Vivek Jayadeva; Raymond Serrano; Karthik Sivashanker (Case Reports in Psychiatry)
Neuroleptic malignant syndrome (NMS), an iatrogenic form of malignant catatonia, carries high morbidity and mortality rates especially in the context of delayed recognition and standard intervention protocol of lorazepam trial. However, there is limited guidance available through literature for further management if benzodiazepine treatment is ineffective and electroconvulsive therapy (ECT) is not readily accessible. This case report describes a multimodal approach to address the diagnostic, treatment, and logistical system challenges in an acute medical hospital through the case of a 69-year-old man with schizophrenia who represented from a psychiatric ward with neuroleptic malignant syndrome. We educated our inpatient colleagues for timely recognition of hyperexcited subtype of catatonia to avoid iatrogenic progression to neuroleptic malignant syndrome and our medical colleagues on the clinical course of catatonic symptoms to avoid any further disagreements and delays in treatment. We advocated for timely electroconvulsive therapy in the setting of limited access and utilized creative pharmacologic strategies such as N-methyl-D-aspartate (NMDA) receptor antagonists and longer acting benzodiazepines while managing medical complications.